Effective thermal parameters of chalcogenide thin films and simulation of phase-change memory - Huang, Yin-Hsien; Hsieh, Tsung-Eong (International journal of thermal sciences, 2015)
Thermal conductivity of Ge2Sb2Te5 (GST) and Ce-doped GST (Ce-GST) chalcogenide thin films and thermal boundary resistances (TBR) at the interface of chalcogenides and thin films such as ZnS:SiO2 and TiN were measured by the 3-omega (3ω) method in conjunction with the plywood-structure samples. The measured results were then implanted in the finite-element simulation for analyzing the thermal conduction behaviors of phase-change memory (PCM) devices. The analysis utilizing a three-dimensional fully coupled electric and thermal model indicated that the TBR at the interface of chalcogenide and TiN contact layer is the key physical property affecting the temperature profile and heating efficiency of PCM cells subject to a pulse heating operation. It was found the TBR significantly alters the temperature uniformity and suppresses the programming current. For instance, the presence of TBRGST/TiN of 7.01 × 10−8 m2 K/W led to a 30% reduction of programming power of PCM cell while the TBRCe-GST/TiN of 8.82 × 10−8 m2 K/W led to a 27% power reduction in comparison with the case without considering the TBR property. As to the doping effect, higher resistivity of Ce-GST layer led to the decrease of programming current (up to 39% reduction in Ireset) and the low thermal conductivity feature of Ce-GST provided a better thermal confinement effect in PCM cells. The simulation results illustrated that the TBR property must be taken into consideration in optimizing the PCM device structure and this limitation could be remedied by the doping in chalcogenide programming layer. •Thermal properties of thin films in PCM devices were measured by 3ω method.•PCM's thermal-electrical behaviors were analyzed by 3-D finite-element simulation.•Thermal boundary resistance at GST/TiN interface reduced heating efficiency of PCM.•Thermal boundary resistance reduced programming electrical power of PCM.•Doping in programming layer alleviated influence of thermal boundary resistance.